(untitled) (Journal of Hama University, 2019)
The dimensions of the dielectric resonators which works in conventional modes through the beam of high frequencies (microwave and optic) like TE01δ are very tiny absolutely. So the use of them is very difficult in the specific accuracy into the circuits and they are not allowed an easy merging in these circuits. So the use of these resonators which called either edging modes or whispering modes (WM), are worked in new modes, because they allow to increase the resonator diameter for the same previous frequencies. The study we are advancing here focuses on a detailed preliminary electromagnetic (Analytic And Numeric) for structures in cylindrical dielectric resonators operating in these modes, for use them later in designing the microwaves passive integrated circuits such as : Combinor of puissance, Filters, Oscillators,…. The achievement of this study requires from us, at first developing calculative analytic study which allows us to identify the dispersion equations for the elements of electromagnetic field that permit to identify approximately the resonance frequencies for different modes . Secondly, the use of numeric calculative method is based on library Modulef programme. That can be done after writing all the necessary and proper codes for each studied structure. Through this phase, it will define accurately for all electromagnetic parameters (resonance frequencies, distribution of electromagnetic field, vide quality factor), Finally, we will study the evolution of vide quality factor as a follower to various structure dimensions. This study will put in front of us all the value of the electromagnetic parameters as a follower to physical and geometrical materials for the studied structures. Through that, we can chose the best to design and execute the practicality circuits for use them in suitable applications, and for us, we will use these results in designing microwave band pass filters in very low loss, narrow band and excellent selectivity